2006
DOI: 10.1088/0953-8984/18/15/001
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric characterization of surface freezing in Ga-based alloys

Abstract: We present results on surface freezing of Ga-based alloys, GaBi, GaPb and GaTl, above the liquidus line between the Ga-rich eutectic and the monotectic point. Spectroscopic ellipsometry (0.8 eV ≤hν≤4.2 eV) and kinetic single wavelength ellipsometry (2.75 eV) have been employed to probe the changes of the interfacial electronic structures on surface freezing. To minimize thermal gradients across the sample a heatable cap that covers the sample and crucible was developed. The surface freezing temperature, TSF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…At this temperature an abrupt change in ∆ from 124° to 115° and in Ψ from 40.5° to 38.25° degree is observed within 45 seconds! The solidification temperature was reproducible in several runs within ±1.5 K. This jump was identified for Ga-Bi, Ga-Pb and Ga-Tl with the formation of a smooth solid surface film [6,9]. The quality of the surface and the reflection alignment is only marginally altered as can be seen by the small change in S 0 .…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…At this temperature an abrupt change in ∆ from 124° to 115° and in Ψ from 40.5° to 38.25° degree is observed within 45 seconds! The solidification temperature was reproducible in several runs within ±1.5 K. This jump was identified for Ga-Bi, Ga-Pb and Ga-Tl with the formation of a smooth solid surface film [6,9]. The quality of the surface and the reflection alignment is only marginally altered as can be seen by the small change in S 0 .…”
Section: Resultsmentioning
confidence: 62%
“…This transition was detected by different spectroscopic methods (second harmonic generation, SHG, [6], surface light scattering [7], x-ray photoelectron spectroscopy, XPS, [8], ellipsometry [9]) and was also found in a model calculation of surface phase transitions in Ga-Bi alloys [10]. Ellipsometric investigations showed that this surface solidification phenomenon is robust with respect to significant temperature gradients across the sample and to a variation of the cooling rate.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations